Role of Emblica officinalis Amla on Nicotine toxicity to rats Rattus orvegicus - Sharief, Dawood (International Journal of Pharmaceutical & Biological Archive, 2014)
Role of Emblica officinalis Amla on Nicotine toxicity to rats Rattus orvegicus